Review on climate change and its effect on wildlife and ecosystem - Quratulann Sattar; Muhammad Ehsan Maqbool; Rabia Ehsan; Sana Akhtar (Open Journal of Environmental Biology - Peertechz Publications, 2021)
This scientific literature contains numerous descriptions of climatic changes and their effect on wildlife and the ecosystem. Biodiversity and climate are interconnected to each other. The previous studies show that changes that occur in climate affect wildlife directly and indirectly. The basic cause of climatic change is human activities. Human activities increase the greenhouse gases which cause the greenhouse effect. The rising temperature of the atmosphere causes thermal optima to shift towards high altitudes and high latitudes. Global precipitation increases in the last few years that also affect the wildlife. Climate changes disturb the dynamic condition by biomass production, trophic interaction, and hydrological balance. Change climate regimes directly affect the wildlife their behavior, reproduction, migration, and foraging. Drivers of phenology such as mating, breeding, hibernation, and post-hibernation activities will benefit some species and disadvantage others this will cause a new ecosystem. Some climate parameters such as photoperiod (Drive life history events) remain the same while the timing of spring weather changed because of greenhouse gases. Some pathogens can also increase their effectiveness with changes in the climate. Climate change danger the native terrestrial wildlife to extension and alters the functions and structure of their ecosystem. Therefore, it's critical to address climate change for biodiversity conservation and ecosystem management.